The Role of Written Corrective Feedback in Enhancing Students’ Proficiency in Writing: Case of Second Year Students,University of Constantine 1 - ZEMIECHE, Amina (Journal of Human Sciences, 2018)
Written corrective feedback is of a crucial role to the improvement of students’ writings.Every time their writing teachers provided them with the feedback, students should not hesitate to make use of it to develop their writing. This study discusses the effects of the different types of written corrective feedback in enhancing students’ writing and at finding out the appropriate type of written corrective feedback to be used. This is done through comparing the results of the effects of three types of corrective feedback on students’ written productions. The hypothesis is that ifstudents are provided with un-coded written feedback, coded written feedback, and peer feedback this would result in effective results on the writing performances of students who receive un-coded corrective feedback in comparison to those who receive coded feedback and peer feedback. To test the validity of this hypothesis, the researcher opted for a questionnaire, directed to teachers of writing in the department of Letters and English Language, at the University of Constantine 1